Pendampingan Dan Konseling Karir: Membantu Siswa Memahami Prospek Pendidikan Lanjutan Dan Karir Yang Tersedia Setelah Lulus - Nur, Rizki Amalia; Rusdi, Hikmah; Pongpalilu, Fien; Ernawati, Ernawati; Nurhidayah, Nurhidayah; Riyanti, Rika; Lestari, Pertiwi Indah; Amalia, Nurul; Septiana, Windy; Ningsi, Sri Fitria Wahyu; Nurwahida, Nurwahida; Zul, Wardania (Pakis Journal Institute, 2024)
Changes in the labor market affect the dynamics of the career planning process for students. Career planning for students is an important thing to develop in supporting the desired goals. Therefore, students need the right career plan so that students can choose a career according to their strengths and talent interests. So that the purpose of Community Service (PKM) activities with the theme of Career Assistance and Counseling is to provide motivation and assistance to students in dealing with their confusion in choosing a career in the future. The method used in this activity is in the form of material delivery and questions and answers between students and presenters. Based on the results of Community Service (PKM) activities at SMA Negri 6 Maros, it is known that students show increased self-confidence and better readiness to face world challenges after graduation. In conclusion, this program succeeded in making a positive contribution, students realized that changes in the job market require them to have high flexibility and adaptability. Interactive Q&A sessions also provided opportunities for students to discuss and share experiences.